CURRICULUM ANALYSIS IN INDONESIA ANALISIS KURIKULUM DI INDONESIA - indah aprilia windiyani; deasy adelia syahrani; meldayanti putri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
This study aims to analyze the development of the education curriculum in Indonesia comprehensively, examine the factors that influence curriculum changes, as well as the challenges and opportunities in its implementation at various levels of education. The method used is qualitative with a literature study approach, namely through the analysis of official documents and related academic literature. The results of the study show that the curriculum in Indonesia has undergone significant changes since the era of independence, starting from the 1947 Curriculum to the 2022 Merdeka Curriculum, which reflects the response to social, political, economic dynamics, and global demands. These changes lead to efforts to improve the quality of education with an emphasis on character development, creativity, and 21st century competencies. However, the implementation of the curriculum still faces obstacles such as inequality between regions, limited resources, and the readiness of educators to adjust learning methods. This study also makes an important contribution to the development of educational science by offering an in-depth understanding of the evolution of an adaptive and visionary curriculum, as a basis for effective policy-making to produce superior and characterful generations.